2022
DOI: 10.3390/foods11071054
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a Multidisciplinary Framework for an Emergency Food Supply System Using a Modified Delphi Approach

Abstract: A scientific food emergency supply system is helpful for assuring food supplies continuity, improving response efficiency, and reducing disaster losses. However, the framework for a food emergency supply system is currently an understudied area in emergency management post-disaster. In this study, a comprehensive literature review of major databases was performed to identify potential indicators for the emergency food supply system, followed by a two-round modified Delphi with a multidisciplinary expert panel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Instead of a distant observation using pre-established observation criteria, it is the closest observation of occupational practice possible. The modified Delphi technique interview and work observation go hand in hand [60][61][62]. The researcher discusses, opens, and explores the intent and applied knowledge to make semi-structured inquiries more understandable.…”
Section: Reference Architecturementioning
confidence: 99%
“…Instead of a distant observation using pre-established observation criteria, it is the closest observation of occupational practice possible. The modified Delphi technique interview and work observation go hand in hand [60][61][62]. The researcher discusses, opens, and explores the intent and applied knowledge to make semi-structured inquiries more understandable.…”
Section: Reference Architecturementioning
confidence: 99%
“…The expert group consisted of 13 participants, despite having reached out to 61 potential participants. The modestly sized expert panel has been supported by several researchers [ 11 , 19 , 32 , 50 , 51 ]. Furthermore, [ 11 ] suggests that 10 to 15 homogenous participants may be enough.…”
Section: Discussionmentioning
confidence: 99%
“…The exploratory nature of our study, rather than increasing group understanding or gaining group support, aligns with the modestly sized participant panel [ 11 ]. Several studies in food research have used similarly sized expert panels to produce consensus documents intended to support future research and practice [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The impact categories that are the focus of this research were initially identified with expert consultation using a qualitative two-round e-Delphi method [ 11 , 12 ] with 13 participants. The first round was used to identify potential impacts of the Russia-Ukraine conflict on food supply chains based on the hypothesis that significant impacts on the effectiveness and responsiveness of global food supply chains are the result of the conflict between Russia and Ukraine.…”
Section: Methodsmentioning
confidence: 99%